Children and parents time use: empirical evidence on investment in human capital in France, Italy and Germany - Ana Rute Cardoso; Elsa Fontainha; Chiara Monfardini (Institute for the Study of Labor (IZA), 2008)
We analyze a mechanism that has been disregarded in the literature on parental investment in children, as little attention has been devoted to the choices made by children themselves. We model directly time use by youngsters into activities related to the acquisition of human capital, considering not just the decision on study time, but also on socialization/networking at young age, which can enhance personal interaction skills. We provide new empirical evidence for three European countries (France, Italy and Germany) on the link between time allocation by parents and time allocation by youngsters, highlighting country-specific patterns as well as cross-country differences. We run fractional regression models and double hurdle models on multi-member household micro data on time use. Countries diverge concerning the association between parents and youngsters allocation of time to socializing and to reading and studying activities, with Italy standing out as the country where that association, in particular between youngster and mother, is strongest. Our results are consistent with different mechanisms: parental role model directly influencing children behavior, intergenerational transmission of preferences, or network effects, as individuals adapt their behavior to social patterns.
urn:nbn:de:101:1-20081127382
Keywords: J22; 330; Study time; socializing; networking; youth; intergenerational transmission of preferences; fractional regression models; double hurdle models; Jugendliche; Zeitbudgetforschung; Bildungsinvestition; Soziale Beziehungen; Familiensoziologie; Generationenbeziehungen; Frankreich; Italien; Deutschland